Pulsation and Vibration Measurement on Stator Side for Turbocharger Turbine Blade Vibration Monitoring - Takashi Ando (International Journal of Turbomachinery, Propulsion and Power, 2020)
Mechanically robust turbine design with respect to blade vibration is challenging when dealing with nozzle-ring fouling and wear. Especially for engines operating with heavy fuel oil (HFO), the nozzle rings of the turbocharger turbines are prone to severe degradation in terms of contamination with unburned fuel deposits. This contamination will lead to an increased excitation of blade resonances in comparison to the nominal design. Due to the statistical character of contamination, long-term monitoring of blade vibration amplitudes would be beneficial. In the harsh environment of HFO operation, however, conventional blade vibration measurement techniques, such as those using strain gauges or blade tip timing, cannot work reliably for a long period. Thus, the objective of this research is to develop a method that enables the monitoring of turbine blades using pulsation or vibration sensors installed on the stator side. Almost a dozen turbines, both radial and axial, have been examined in order to determine a proper measurement chain/position and analytical method. Even though the challenges specific to the turbocharger turbine application—that high-frequency (up to 50 kHz) acoustic radiation from turbine blades has to be detected by a sensor on the stator side—were demanding, in the course of the investigations several clear examples of turbine blades engine-order resonance detection were gathered. Finally, the proposed method has been tested successfully in a power plant for over one year.